Transient temperature field in thick-film multilayer structures - Błąd, Grzegorz; Hotra, Zenon; Klepacki, Dariusz; Potencki, Jerzy (Видавництво Національного університету «Львівська політехніка», 2002)
The paper presents two methods of temperature field simulation in thick-film multilayer structure with local pulse heating. The first method is based on the equivalent electrical model of heat transfer. Simulations have been made using PSPICE program. The basis of the second one is solving the heat equation through integral transforms. Calculations were made on example thick-film laser power detector.
Keywords: temperature field; thick-film; echnology